Prognostic relevance of the triglyceride–glucose index in patients after thrombectomy for acute anterior circulation occlusion - Wang, Zhongxiu; Wang, Siyuan; Li, Chao; Song, Kangjia; Wu, Xiaoyu; Jiang, Yu; Zhang, Mingchen; Wang, Shouchun (Frontiers in Neurology, 2025)
BackgroundWe aimed to investigate the relationship between the triglyceride–glucose (TyG) index and the 3-month prognosis after mechanical thrombectomy (MT) in patients with acute large-vessel occlusion in the anterior circulation.MethodsWe performed a retrospective analysis of data collected from 320 patients who underwent MT at our institution between May 2022 and January 2024. The main outcome measure was the modified Rankin Scale (mRS) score, with a score of ≤2 at 90 days post-treatment indicating a good prognosis. Secondary outcomes were the 90-day mRS score distribution, 24-h postoperative National Institutes of Health Stroke Scale (NIHSS) score, and NIHSS score at discharge. Safety outcomes were 90-day mortality, intracranial hemorrhage (symptomatic and asymptomatic), and surgical complications.ResultsOne hundred and eight patients (33.8%) achieved functional independence at 90 days. After adjusting for covariates, patients who fell within the second group of the TyG index exhibited a lower probability of functional independence than those in the first group (adjusted odds ratio [aOR] = 0.450; 95% confidence interval [CI], 0.257–0.789; p = 0.005). Additionally, an increase of one unit in the TyG index was significantly correlated with a 33% reduction in the likelihood of achieving functional independence at 90 days postoperatively (aOR = 0.669; 95% CI: 0.450–0.996; p = 0.048).ConclusionThis study demonstrates that the TyG level was significantly related to achieving functional independence within 90 days among patients who have undergone MT for acute anterior circulation infarction. Based on traditional neurological function (e.g., NIHSS) assessments, the TyG index may be used as an independent prognosis predictor after thrombectomy in patients with acute ischemic stroke.